Child abuse profiles in a Soweto abuse centre - Mwanda, Nobulembu Babalwa (My University, 2014)
The aim of this study was to examine the profiles of child abuse in Zamokuhle Child Centre, a child abuse referral Centre serving black children in Soweto. It was hypothesised that these profiles are different from those described in the Western communities. A retrospective analysis of all 1995 patient records was done. The data was extracted by the way of a data collection form. A total of 372 children were seen over a ten-month period in which the Centre was operational. Of these records all but four could be traced. Of the 368 records, 357 were related to sexually abuse. There were very few cases of other forms of abuse. The average age of these children was 8.1 ± 3 .6 years and 97% were females. Only in about a third of these children was abuse purposefully disclosed, either to mother (29.7% ) or teacher (17.8%). M ost of the children (61.3% ) were incidentally found to be abused by either a clinician (57.1% ) or a parent (27.9%). Most children presented with signs and symptom s that raised enough suspicion of sexual abuse. An overwhelming majority (278 out of 357) had physical signs highly suggestive of penetration beyond the hymen, on examination. Only in about a third of the cases was the abuse intra-familial, in the majority it was extra-familial. STDs were diagnosed in about 12% of the children.
Keywords: Child Abuse